Microsoft Access 2010 VBA macro programming - Shepherd, Richard (New York : McGraw-Hill, 2011)
'Perfect for power users, Microsoft Access 2010 VBA Macro Programming reveals how to maximize the features and functionality of Access 2010. You'll get in-depth details on Access VBA programming and application development followed by 20 real-world projects--complete with source code--that show you how to set up specific subroutines and functions. This practical resource then explains how to include the subroutines in the Access menu system and transform a set of interrelated VBA macros into an Access add-in package. Create your own Access 2010 VBA macros right away with help from this hands-on guide'--Provided by publisher.
Includes index.
Keywords: Microsoft Access; Microsoft Visual BASIC; Database management